TOPICAL AND SYSTEMIC DERMAL CARRIERS FOR PSORIASIS - Abdelgawad, Rana; Nasr, Maha; Hamza, Manal Yassin; Awad, Gehanne A. S. (International Journal of Current Pharmaceutical Research, 2016)
Psoriasis is a non-infectious, dry, inflammatory (autoimmune) skin disorder. Treatment approaches include phototherapy, topical, oral and other systemic drug delivery. However, owing to the side effects and incomplete cure accompanying the oral administration as well as phototherapy, the topical route seemed to be more satisfactory for the medical team. Dermal treatment ensuring percutaneous penetration is now highly recommended in topical indications for psoriatic patients, which can be achieved using pharmaceutical carriers. Several carrier systems loaded with antipsoriatic drugs have demonstrated promising results, with some of them strictly being confined to the skin and others allowing for systemic involvement also. The evolution in this area will present a more useful and safer therapy by minimizing the drugs' degradation and loss, and increasing their bioavailability and effectiveness. Since patients require at least three topical applications for almost a 1-year period to gain health benefit, a reduction in the cost of the treatment will be of real value. A distinction of these carriers is made in the current review, to allow the choice of the most suitable pharmaceutical carrier for psoriatic patients requiring either local and/or systemic involvement.